The Bladder Pill: Developments Toward Bladder Pressure Measurement in Wake Mini-pigs. (2016) - Bakula, M.; Soebadi, A.; De Ridder, D.; Puers, R.
Abstract: This work presents progress on development of the "Bladder pill", a pressure monitoring implant for urological diagnosis. The device, measuring as little as 5x30 mm, uses resonant inductive coupling for wireless powering and communication via an omnidirectional "3-D" receiving coil. The transmitting coil along with the battery-powered control and data logging circuitry is integrated into an external belt suitable for in-vivo testing in mini-pigs. All circuitry is realized using low cost off-the-shelf components, including the pressure sensor which is decapsulated to allow potting in PDMS. Powering and communication is successfully achieved at a distance up to 12 cm orthogonally from the belt with data rates exceeding 10kbps and pressure sampling rate of 10 Hz with < 2.5W power input. Finally, the results of a preliminary test involving a measurement of bladder contractions and voiding in anaesthised mini-pigs are presented and discussed.